2012
DOI: 10.1111/j.1742-7843.2012.00903.x
|View full text |Cite
|
Sign up to set email alerts
|

Coffee and Caffeine Protect against Liver Injury Induced by Thioacetamide in Male Wistar Rats

Abstract: Coffee intake has been inversely related to the incidence of liver diseases, although there are controversies on whether these beneficial effects on human health are because of caffeine or other specific components in this popular beverage. Thus, this study evaluated the protective effects of coffee or caffeine intake on liver injury induced by repeated thioacetamide (TAA) administration in male Wistar rats. Rats were randomized into five groups: one untreated group (G1) and four groups (G2-G5) treated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
65
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 47 publications
6
65
2
1
Order By: Relevance
“…This comes into agreement with the results of previous investigators who reported the heptoprotective effect of coffee and caffeine against liver injury induced by thioacetamide in male Wistar rats [23]. In addition, the antifibrotic action of caffeine was evaluated in our study by reducing the hepatic content of hydroxyproline which is an indicator for the deposition of collagen and this result are in harmony with that of previous investigators who reported an experimental evidence for the protective effects of coffee against liver fibrosis in sprague dawley (SD) male rats [24].…”
Section: Discussionsupporting
confidence: 82%
“…This comes into agreement with the results of previous investigators who reported the heptoprotective effect of coffee and caffeine against liver injury induced by thioacetamide in male Wistar rats [23]. In addition, the antifibrotic action of caffeine was evaluated in our study by reducing the hepatic content of hydroxyproline which is an indicator for the deposition of collagen and this result are in harmony with that of previous investigators who reported an experimental evidence for the protective effects of coffee against liver fibrosis in sprague dawley (SD) male rats [24].…”
Section: Discussionsupporting
confidence: 82%
“…Liver fibrosis was induced according to the method of Esmat et al [23] and Furtado et al [24]. Fourty two male SpragueDawly rats were intraperitoneally (i.p.)…”
Section: Induction Of Liver Fibrosismentioning
confidence: 99%
“…The previous scientific information about caffeine shows it is a psychoactive and hypoalgesic substance, it stimulates breathing and dilates the bronchi and has anti-oxidant/anti-inflammatory effects which protect liver and other tissues [4347]. Moreover, it reduces liver induced insulin resistance [48].…”
Section: Discussionmentioning
confidence: 99%
“…Caffeine improves psychomotor performance and increases self-reported alertness and decreases self-reported weariness and sleepiness. Coffee per se or its specific compounds contain antioxidant properties and have protective effects against oxidative DNA damage, liver lesions (hepatotoxicant induced fibrosis) and tissue damage [47]. Coffee consumption also attenuates liver induced insulin resistance [48].…”
Section: Introductionmentioning
confidence: 99%